Optimization study of SiO2-Al2O3 supported bifunctional acid–base NiO-CaO for renewable fuel production using response surface methodology. (1st June 2017) - Asikin-Mijan, N.; Lee, H.V.; Taufiq-Yap, Y.H.; Abdulkrem-Alsultan, G.; Mastuli, M.S.; Ong, Hwai Chyuan
Graphical abstract: Highlights: CaO-NiO5 /SiO2 -Al2 O3 catalyst shows acidity-basicity active sites for deoxygenation. The catalyst shows high catalytic activity with paraffin (C8 –C20 ) yield of >70%. Decarboxylation is the main pathway with majority yield of C17 . Optimization showed positive response for effect of temperature-catalyst amount. The catalyst showed high reusability (>65%) for 4 consecutive cycles. Abstract: Optimization study on NiO-CaO5 /SiO2 -Al2 O3 catalysed deoxygenation of triolein towards paraffin yield was investigated. Response surface methodology-central composite design (RSM-CCD) was used to design the experiments with three operating parameters: catalyst loading (1–9 wt.%), reaction temperature (270–390 °C) and reaction time (30–150 min). The present study indicated that maximum yield of straight chain hydrocarbons (73.3%) was achieved under deoxygenation condition of 7 wt.% of catalyst, 340 °C within 60 min, which the interaction effect between reaction temperature-catalyst amount greatly influenced the straight chain hydrocarbons yield. In addition, the generated RSM model was statistically significant and adequate to predict the results with minimum error of <4%. The NiO-CaO5 /SiO2 -Al2 O3 catalysed deoxygenation of triolein was mainly occured in decarboxylation/decarbonylation(deCOx) pathways of decomposed oleic acid, which lead to the majority of straight chain hydrocarbons at carbon ranged of C17. Furthermore, the NiO-CaO5 /SiO2 -Al2 O3 catalyst showed high reusability with maintained the straight chain hydrocarbons yield (>65%) for 4 consecutive reaction cycles.